Strategic partnerships as a modern form of business integration in industry - I. V. Androsova; O. V. Sogacheva (Вестник университета)
The article considers the role of strategic partnerships in the practice of integration interactions of industrial enterprises in the modern economic environment. The authors highlight the distinctive features of strategic partnerships from other forms of business integration. The paper ascertains that for industrial enterprises, strategic partnerships based on the mechanism of subcontracting are most applicable. The study develops a model of strategic partnership based on subcontracting. The article gives practical examples of creating strategic partnerships. The paper analyses the level of development of strategic partnerships in industry, as well as studies the infrastructure that provides this process. The authors focus on the problems that hinder the activation of the processes of creating strategic partnerships based on subcontracting in the regions. Based on the results of the article, the authors offer recommendations aimed at the successful implementation of the creation of strategic business partnerships in industry.